Pengaruh Perputaran Modal Kerja, Perputaran Piutang Dan Perputaran Kas Terhadap Profitabilitas Pada Perusahaan Properti Dan Real Estae Yang Terdaftar Di Bei - Stevanny Yuwono Sinaga; Anita Permatasari (Jurnal Trial Balance, 2025)
Profitability is one of the important aspects for a company in showing its ability to gain profit and maintain its competitiveness. Profitability also plays an active role in ensuring the company's financial stability in the long term. The proxy for profitability is by using Return on Assets (ROA). This study will discuss three factors that can affect a company's profitability. The three factors are working capital, accounts receivable turnover and cash turnover. The data used in this study are secondary data taken from financial statements listed on the Indonesia Stock Exchange from 2021 to 2023. The population of this study is property and real estate companies listed on the Indonesia Stock Exchange from 2021 to 2023. The sampling technique used is purpose sampling. The criteria are the first property and real estate companies listed on the Indonesia Stock Exchange in 2021-2023. The second criterion is that the required financial report information for property and real estate companies is incomplete during 2021-2023. The third criterion is property and real estate companies that have not made a profit for three consecutive years. Based on the criteria, the number of samples obtained was 47 out of 78 companies. The analysis technique in this study used multiple linear regression tests and was processed using the SPSS Statistics program. There are two types of variables used in this study, namely the dependent variable is profitability (Y) and the independent variables are working capital turnover (X1), accounts receivable turnover (X2), and cash turnover (X3). The results of this study state that the work model does not affect profitability in property and real estate companies listed on the Indonesia Stock Exchange in 2021-2023. The second research result states that accounts receivable turnover does not affect profitability in property and real estate companies listed on the Indonesia Stock Exchange in 2021-2023. The third research result states that cash turnover affects profitability in property and real estate companies listed on the Indonesia Stock Exchange in 2021-2023. Keywords: Working Capital Turnover, Receivables Turnover, Cash Turnover